Uganda : Policy Note on Social Accountability - Bitekerezo, Mary; De Berry, Joanna; Shalita, Steven (World Bank, Washington, DC, 2014)
This policy note is based on a wider study that analyzed how various stakeholders in Ugandan society can better engage to improve social accountability in service delivery. The study conducted a rapid assessment of selected public officials in three districts (Bushenyi, Lira, and Mukono), non-governmental organizations (NGOs) and other civil society organizations, media associations, and parliamentary committees. Focus group discussions with members of selected community-based organizations were also held in the three districts. It also included an in-depth study of selected community-based organizations, brief literature reviews and a public opinion poll. The policy note synthesizes the report's main findings and focuses on key policy recommendations. It is intended as an input into ongoing dialogue and a number of processes and efforts that aim to strengthen civil society participation to improve governance in service delivery in Uganda.